Public administration archives: state of the art of record management and classification systems - Elisabetta Reale (JLIS.it, 2017)
The contribution is aimed at presenting the state of art related to the records management in the public sector and, more specifically, to the main tools required for managing current records according to the Direction general for Archives and its specific competencies which imply a role for defining and approving classification and preservation plans. The article analyses various projects developed for the public sectors in the last 25 years in connection with the innovation processes for the public administration and the crucial role recognised to the records management. The paper illustrates the work done by working groups for universities, municipalities, regions and provinces but also for health environment, chambers of trade, banks and educational institutions. With reference to the State institutions, a general picture is presented for ministries such as Ministry of Justice and Ministry for cultural heritage. In the last case, the classification system developed and adopted in 2004 in connection with the electronic registry system is discussed in detail. The paper presents also the project supported by the Agenzia dell’Italia digitale (AGID) dedicated to the definition of a common classification plan for administrative functions in the public sector. Even if not complete the picture is able to provide elements to evaluate the tools and their critical aspects, to stress the need for cooperation, to update the present systems and study general methodologies. The contribution is also dedicated to the role of professionals with specific experience in the records management systems for the public sector.